"Macro transcobalamin causing raised vitamin B12: Case-based laboratory investigation". (July 2022) - Duim, Sjoerd N.; Vlasveld, L. Tom; Mezger, Stephanie T.P.; Mingels, Alma M.A.; Ramakers, Christian R.B.; de Boer, Douwe; Heil, Sandra G.; Nexo, Ebba; van Rossum, André P.
Determination of plasma vitamin B12 (B12) is a frequently requested laboratory analysis, mainly employed to establish B12 deficiency. However, an increased level of B12 is a common unexpected finding that may be related to an increased concentration of one of the B12 binding proteins, haptocorrin or transcobalamin. This paper describes the extensive laboratory evaluation of a patient with an elevated level of plasma B12 with various well-established assays. Initial studies suggested the presence of a macromolecule consisting of haptocorrin bound B12. Specific determinations of the B12-binding proteins revealed normal amounts of haptocorrin but a markedly increase in both total and B12 saturated transcobalamin (holo-TC). The results are in accord with the presence of macro-transcobalamin. These experiments reveal that determination of the nature of the B12-macromolecules is troublesome due to differences in assays applied to measure these proteins. In addition, this publication creates awareness of macro-holo-TC as a cause of an unexplained increased B12 level.